Overcoming plagiarism through habituation on appreciating each human work: Balinese culture implementation of Tri Hita Karana on learning in higher education - Wulandari, I Gusti Agung Ayu; Lasmawan, I Wayan; Suarni, Ni Ketut; Margunayasa, I Gede (Nurture, 2024)
Purpose: Tri Hita Karana is one ofthe three causes of happiness in the lives of Balinese people. The cause of this happiness is a harmonious and good relationship between humans and (1) God or the Creator, (2) other humans, and (3) the surrounding environment. This study aimed to describe that THKhabituation affects simultaneously both students’ academic honesty and social honesty. Design/Methodology/Approach: This research is a type of quantitative research with 296 population students, in which 56 students were randomly selected and divided into two classes. The data collection method used a non-test with a questionnaire as the instrument. Data were analyzed using Multivariate Analysis of Variance (MANOVA) Findings: There is a significant difference in academic and social honesty simultaneously between the students who were involved in THK and those who participated in common habituation. This shows that applying THK habituation continuously during lectures could prevent plagiarism. The final result shows that this habituation affects positively scientific practices, in which the previous high plagiarism percentage of 90% decreased to 24%. Conclusion: THK habituation affects the academic and social honesty of the students positively. No wonder it happens because this habituation is applied continuously and emphasized verbally. It is also supported by a study that conveys that future academic violations can be prevented by increased support and good guidance while the students learn.